A Robust Nonlinear Control Strategy for Unsupported Paraplegic Standing Using Functional Electrical Stimulation: Controller Synthesis and Simulation - Ruhbakhsh, Seyedeh Sakineh; Kobravi, Hamid Reza (International clinical neuroscience journal, 2020)
Background: Functional electrical stimulation (FES) applies electrical pulses to paralyzed muscles to restore their function. Closed-loop control of an FES system, incorporating the control strategies, promises to improve the performance of FES systems. Therefore, the purpose of this paper is to design a new control strategy applicable to restoring the upright standing in paraplegic patients through FES. The control strategies proposed in the previous works based on controlling the angular joint position and none of them focused on controlling the center of pressure (CoP) dynamics directly. Since the CoP is representative of posture balance dynamics, in this study, the adopted FES based control strategy designed to control the CoP dynamics directly. Methods: In the proposed control strategy, two controllers determine the stimulation intensity of ankle muscles in a manner to restrict the CoP to a specific zone. According to the proposed strategy, until the CoP confined to the stable zone, an adaptive controller is active. When the CoP goes out of the stable zone, the adaptive controller is deactivated. Then, a sliding mode controller is activated instead of the adaptive controller. In this manner, not only the posture balance can be guaranteed, but also the emerged balance dynamics can be similar to the elicited balance dynamics in the healthy subjects. Results: In this study, extended evaluations carried out through the simulation studies. According to the achieved results, the proposed control strategy is not only robust against the external disturbances, but also insensitive to the initial postural conditions. Conclusion: The achieved results prove the acceptable performance of the proposed control strategy